Studi Etnobotani Tanaman Pekarangan Rumah di Kecamatan Mungka, Sumatera Barat: Penelitian - Tahirah, Rahmatya; Fitri, Rahmadhani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the types of plants that can be found in home gardens by the community in Mungka District, West Sumatra, using an ethnobotanical approach. The study focuses on identifying the types of cultivated plants, the utilization of home garden plants, their distribution, and the conservation status of these plants. The method used in this study was direct observation of the informants. The results of the study reveal that backyard plants in Mungka District exhibit a high level of species diversity and are utilized in various ways, ranging from food sources, ornamental plants, to traditional medicine. It is hoped that the findings of this study will contribute to efforts in preserving traditional knowledge and managing biodiversity in the region.